Systemic-Structural Nuclear Family Profile Of Families At Hermilio Valdizan Hospital - Mendoza, Alfonso (1996)
This paper studies the Structural Family System Profile of twenty nuclear families, in which one nuclear member is a new outpatient of a public psychiatric hospital. Structural Family System Rating is used as an instrument to asses the family in five dimensions: structure, developmental stage, resonance, identified patienhood and conflict resolution. The results show a global significant disfunctionality, especially in conflict resolution, identified patienthood and structure. We compare these results with others studies.